The strategic university management and its influence in the positioning of the Licensed in Administration of the National University Jorge Basadre Grohmann of Tacna-2018 - Gómez Caceres, Felipe (2021)
The objective of this research was to determine to what extent  university strategic management influences the positioning of the graduate in Administration of the Universidad Nacional Jorge Basadre Grohmann de Tacna in 2018. The investigation was basic, descriptive-explanatory in nature. We work with a sample of 574 members of the university community among teachers, administrators and graduates in Administration of the  UNJBG; who through the application of the questionnaire provided data to measure the variables of the present study. The  instrument to measure the variables consisted of 26 items; it was designed by Lozano (2013), but was adapted for the present  research. Likewise, it has expert validation, reliability analysis using Cronbach's alpha and item correlation analysis. After the data collection and processing, through the SPSS V.22 statistical software, the results obtained for each item and corresponding variable were described. The hypotheses were accepted with the results validated through parametric tests conducted by the Kolomogorov-Smirnov test. In addition, the Chi-square test and contingency coefficient allowed concluding that there is a significant "high" influence of university strategic  management on the positioning of the graduate in Administration of the Jorge Basadre Grohmann National  University of Tacna.